Aberrant signalling by protein kinase CK2 in imatinib‐resistant chronic myeloid leukaemia cells: Biochemical evidence and therapeutic perspectives. Issue 6 (22nd August 2013) - Borgo, Christian; Cesaro, Luca; Salizzato, Valentina; Ruzzene, Maria; Massimino, Maria Lina; Pinna, Lorenzo A.; Donella-Deana, Arianna
Abstract : Chronic myeloid leukaemia (CML) is driven by the fusion protein Bcr‐Abl, a constitutively active tyrosine kinase playing a crucial role in initiation and maintenance of CML phenotype. Despite the great efficacy of the Bcr‐Abl‐specific inhibitor imatinib, resistance to this drug is recognized as a major problem in CML treatment. We found that in LAMA84 cells, characterized by imatinib‐resistance caused by BCR‐ABL1 gene amplification, the pro‐survival protein kinase CK2 is up‐regulated as compared to the sensitive cells. CK2 exhibits a higher protein‐level and a parallel enhancement of catalytic activity. Consistently, CK2‐catalysed phosphorylation of Akt‐Ser129 is increased. CK2 co‐localizes with Bcr‐Abl in the cytoplasmic fraction as judged by subcellular fractionation and fluorescence immunolocalization. CK2 and Bcr‐Abl are members of the same multi‐protein complex(es) in imatinib‐resistant cells as demonstrated by co‐immunoprecipitation and co‐sedimentation in glycerol gradients. Cell treatment with CX‐4945, a CK2 inhibitor currently in clinical trials, counteracts CK2/Bcr‐Abl interaction and causes cell death by apoptosis. Interestingly, combination of CX‐4945 with imatinib displays a synergistic effect in reducing cell viability. Consistently, knockdown of CK2α expression by siRNA restores the sensitivity of resistant LAMA84 cells to low imatinib concentrations. Remarkably, the CK2/Bcr‐Abl interaction and the sensitization towards imatinib obtained by CK2‐inhibition in LAMA84 is observable also in other imatinib‐resistant CML cell lines. These results demonstrate that CK2 contributes to strengthen the imatinib‐resistance phenotype of CML cells conferring survival advantage against imatinib. We suggest that CK2 inhibition might be a promising tool for combined strategies in CML therapy. Highlights: CK2 signalling is up‐regulated in imatinib‐resistant as compared to sensitive chronic myeloid leukaemia cells. CK2 and Bcr‐Abl co‐localise and are interacting proteins. Inhibition of CK2 causes cell death by apoptosis of chronic myeloid leukaemia cells. Down‐regulation of CK2 signalling can overcome the imatinib‐resistance.